2018
DOI: 10.1530/jme-17-0195
|View full text |Cite
|
Sign up to set email alerts
|

Intact glucose uptake despite deteriorating signaling in adipocytes with high-fat feeding

Abstract: To capture immediate cellular changes during diet-induced expansion of adipocyte cell volume and number, we characterized mature adipocytes during a short-term high-fat diet (HFD) intervention. Male C57BL6/J mice were fed chow diet, and then switched to HFD for 2, 4, 6 or 14 days. Systemic glucose clearance was assessed by glucose tolerance test. Adipose tissue was dissected for RNA-seq and cell size distribution analysis using coulter counting. Insulin response in isolated adipocytes was monitored by glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 50 publications
9
28
1
Order By: Relevance
“…Western blot analysis demonstrated that the protein levels of caveolin-1 and EHD2 had increased three- and twofold, respectively, after 14 d of high-fat diet (HFD) (Figure 1B). While the protein level of caveolin-1 rapidly increased after 2 d, the EHD2 level increased after 14 d, a time point that we previously (Hansson et al , 2018) demonstrated to coincide with considerable adipocyte differentiation. Next, by comparing the EHD2 levels in adipose tissue versus isolated adipocytes from chow- or HFD-fed mice, we found that the increase of EHD2 in adipose tissue following HFD was not due to an increase in the isolated adipocytes (Figure 1C).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Western blot analysis demonstrated that the protein levels of caveolin-1 and EHD2 had increased three- and twofold, respectively, after 14 d of high-fat diet (HFD) (Figure 1B). While the protein level of caveolin-1 rapidly increased after 2 d, the EHD2 level increased after 14 d, a time point that we previously (Hansson et al , 2018) demonstrated to coincide with considerable adipocyte differentiation. Next, by comparing the EHD2 levels in adipose tissue versus isolated adipocytes from chow- or HFD-fed mice, we found that the increase of EHD2 in adipose tissue following HFD was not due to an increase in the isolated adipocytes (Figure 1C).…”
Section: Resultssupporting
confidence: 56%
“…First, we examined the relationship between caveolin-1 and EHD2 expression in adipose tissue using RNA sequence data previously obtained from adipose tissue during a short-term (14 d) overfeeding study in mice (Hansson et al , 2018). By analyzing that data set, we found a positive correlation between EHD2 and caveolin-1 mRNA expression (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the intrinsic regulation, the architecture of adipocytes was also influenced by extracellular factors. Overnutrition induced by short-term overfeeding in mice rapidly causes onset of cellular insulin resistance in adipocytes [134], marked by impaired insulin signaling at the level of insulin receptor substrate (IRS)-1 [135,136] and Akt [137]. Besides, IQ motif containing GTPase activating protein 1 (IQGAP-1) is reduced.…”
Section: Development Of "Supersized" Lipid Dropletmentioning
confidence: 99%